Therapeutic whole blood exchange in the management of methaemoglobinemia: Case series and systematic review of literature. Issue 3 (3rd February 2020) - Singh, Pawan; Rakesh, Kodati; Agarwal, Ritesh; Tripathi, Paramatma P.; Dhooria, Sahajal; Sehgal, Inderpaul S.; Prasad, Kuruswamy T.; Hans, Rekha; Sharma, Rattiram; Sharma, Navneet; Lad, Deepesh; Aggarwal, Ashutosh N.; et al.
Abstract: Background: Therapeutic whole blood exchange (TWBE) has been used as an alternative when methylene blue (MB) fails in severe methaemoglobinemia. However, there are limited data on the efficacy and safety of TWBE. Objectives: Our aim was to report our institutional experience with TWBE. We also perform a systematic review of published literature. Methods: We retrospectively reviewed our respiratory intensive care unit database to identify cases of methaemoglobinemia managed with TWBE. A systematic review of the PubMed database was performed to identify similar cases (≥12 years). We report the indications, utility, and safety of therapeutic exchange in methaemoglobinemia. The procedural details were also noted. Results: We identified five subjects who received TWBE for methaemoglobinemia (median methaemoglobin level 39%; range 19.6‐42.4%). TWBE was successful in all five cases and no adverse events were encountered. Our review identified 27 additional subjects. The median methaemoglobin level was 37.5% (range 3.7‐81%). The most common indication (n = 24, 75%) for therapeutic exchange was a lack of response to MB. A majority of the subjects (n = 26/32, 81.2%) survived. No procedure‐related complications were reported. Conclusion: TWBE is a safe and effective salvage modality for adults with methaemoglobinemia, when MB is either contraindicated or ineffective. Future studies should standardise therapeutic exchange in the management of methaemoglobinemia.